Potential health effects of the popular compound of artichoke: Cynarin (CYN) - Gezer, Ceren (Progress in Nutrition, 2017)
Functional food components are usually related with disease prevention. Cynarin is one of the biologically active functional food components which is the major dicaffeoylquinic acid derivative found in artichoke. Although artichoke contains very low amount of cynarin, it still duplicates the effects of artichoke. Cynarin is one of the biologically active functional food components that have potential effects on choleretic and cholesterol lowering, hepatoprotective, anti-atherosclerotic, anti-HIV, antioxidative, anti-diabetic, anti-carcinogenic and immune modulator activity. To sum up, more molecular, clinical and epidemiological studies on cynarin is necessary to be able to use it as a disease preventive agent.